Mônica vai jantar - Boaventura, Davi Oliveira (2015)
Outcome of a pioneering experience in Brazil, the Creative Writing postgraduate program of Pontifícia Universidade Católica do Rio Grande do Sul (PUCRS), this dis-sertation presents a two level composition: a fictional story, Mônica Vai Jantar, un-published and written during the master’s degree period, and a complementary reflexive essay, here serving as an afterword. Mônica Vai Jantar is a novelette, having stream of consciousness as literary basis, or, specifically, a narrated monologue, containing a sin-gle long sentence, in which I use only commas as punctuation mark, along with rare question marks. It tells the mind confusion of a character that, while preparing for a party, finds out her husband was masturbating inside a bus. The essay, in its own turn, never a step-by-step follow up, is a short narrative route of my influences, doubts, deci-sions, difficulties, authorial references, theoretical references, fictional and personal conversations that helped me through the writing of this work.